2022
DOI: 10.3390/ma15249062
|View full text |Cite
|
Sign up to set email alerts
|

Repair Bond Strength of Conventionally and Digitally Fabricated Denture Base Resins to Auto-Polymerized Acrylic Resin: Surface Treatment Effects In Vitro

Abstract: Denture base fracture is one of the most annoying problems for both prosthodontists and patients. Denture repair is considered to be an appropriate solution rather than fabricating a new denture. Digital denture fabrication is widely spreading nowadays. However, the repair strength of CAD-CAM milled and 3D-printed resins is lacking. This study aimed to evaluate the effect of surface treatment on the shear bond strength (SBS) of conventionally and digitally fabricated denture base resins. One l heat-polymerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
4
19
0
2
Order By: Relevance
“…It has been suggested that a variety of micromechanical surface modification techniques and chemical surface treatment through adhesive systems can improve the ability to repair bonds in acrylic resin repaired using resin composite [16][17][18]. Additionally, surface treatment of acrylic resin with MMA (methyl methacrylate) has been shown to enhance the bonding ability of acrylic resin when repaired with resin composite [5,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a variety of micromechanical surface modification techniques and chemical surface treatment through adhesive systems can improve the ability to repair bonds in acrylic resin repaired using resin composite [16][17][18]. Additionally, surface treatment of acrylic resin with MMA (methyl methacrylate) has been shown to enhance the bonding ability of acrylic resin when repaired with resin composite [5,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Podczas frezowania dochodzi do strat materiału, w przeciwieństwie do druku 3D, który jest procesem bardziej wydajnym, pozwalającym na pozyskiwanie większych obiektów o dowolnym kształcie. 1,12,19,20 Szeroko opisywane w piśmiennictwie jest wykorzystanie metod cyfrowych do projektowania i wytwarzania stałych uzupełnień protetycznych, komponentów implantologicznych, takich jak: szablony, indywidualne łączniki czy elementy precyzyjne, oraz coraz częściej również uzupełnień ruchomych. 1,21,22 Po resekcji tkanek w zakresie podniebienia wskazane jest jak najszybsze uzupełnienie powstałego ubytku w celu przywrócenia funkcji i poprawy jakości życia.…”
Section: Wykorzystanie Technologii Cyfrowych W Rehabilitacji Protetyc...unclassified
“…Zastosowanie monomeru zwiększało siłę wiązania w próbkach polimeryzowanych termicznie i frezowanych, natomiast wszystkie materiały poddane piaskowaniu wykazywały wyższą siłę wiązania z materiałem do naprawy. 20 W badaniach przeprowadzonych przez Awad i wsp. oceniano między innymi siłę wiązania elastycznych (Coe Soft, GC, Japonia i PermaSoft, Dentsply Sirona, USA) i twardych (Tokuyama Rebase II, Tokuyama Dental, Japonia; Kooliner, GC, Japonia i ProBase Cold, Ivoclar Vivadent, Liechtenstein) materiałów do podścielania protez z materiałami na płyty protez frezowanymi (IvoBase CAD, Ivoclar Vivadent, Liechtenstein) i drukowanymi (Denture Base LP Resin; Formlabs Inc, USA).…”
Section: Wykorzystanie Technologii Cyfrowych W Rehabilitacji Protetyc...unclassified
“…Among them, acrylic, PCISO, and Somos EvoLVe 128 are often used in medical fixtures and injection instruments while stainless steel is commonly used in body implantable devices. 1418…”
Section: Introductionmentioning
confidence: 99%
“…Among them, acrylic, PCISO, and Somos EvoLVe 128 are often used in medical fixtures and injection instruments while stainless steel is commonly used in body implantable devices. [14][15][16][17][18] The average shear stress of the normal circulatory system in the human body is approximately 1-7 Pa. [19][20][21][22][23] To exclude the blood damage caused by supraphysiological shear stress, the two experimental platforms in this study were controlled within the range of physiological shear stress. In addition, most of the previous studies only focused on blood damage induced by materials in a static state.…”
Section: Introductionmentioning
confidence: 99%